2013
DOI: 10.1504/ijipm.2013.057634
|View full text |Cite
|
Sign up to set email alerts
|

What impact does intellectual property have on the business performance of technology firms?

Abstract: This paper reports the results of an original empirical study of the relationship between intellectual property and the financial performance of technology firms in the bioscience-technology industries. The study found a statistically significant positive relationship between the firms' investments in intellectual property and their performance. The performance measure was based upon revenue-growth data collected from each firm, and the categories of intellectual property analyzed included patents, trade secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Our findings clearly show that non-patentable inventions too can create incentives for inventors and even entail in general higher role intensities compared with patentable IP (Table 3). Consequently, our findings do not support the sectorial or contextual argument (Artz et al, 2010;Willoughby, 2013) at least not in medical field, where both patentable and non-patentable inventions seem to create incentives for inventors, although future profits are clearer in patentable IP and create monopoly power (Clancy and Moschini, 2013). This is an important contribution towards improving our understanding of innovation processes aiming to exploit non-patentable IP in such important fields as medicine.…”
Section: Other Factors and Inventor Rolescontrasting
confidence: 71%
See 1 more Smart Citation
“…Our findings clearly show that non-patentable inventions too can create incentives for inventors and even entail in general higher role intensities compared with patentable IP (Table 3). Consequently, our findings do not support the sectorial or contextual argument (Artz et al, 2010;Willoughby, 2013) at least not in medical field, where both patentable and non-patentable inventions seem to create incentives for inventors, although future profits are clearer in patentable IP and create monopoly power (Clancy and Moschini, 2013). This is an important contribution towards improving our understanding of innovation processes aiming to exploit non-patentable IP in such important fields as medicine.…”
Section: Other Factors and Inventor Rolescontrasting
confidence: 71%
“…Some findings also indicate that the importance of patents may be dependent on the context (Artz et al, 2010) or the sector (Willoughby, 2013), implying that patents are more important for some context or sectors. Indeed, the impact of patentability is especially highlighted in medical research where patentable IP is viewed as a requirement for commercial exploitation (Colyvas et al, 2002;Garber et al, 2006;Pressman et al, 2006;Smith Hughes, 2001).…”
Section: Ipr Ownership and The Behaviour Of Academic Inventorsmentioning
confidence: 99%
“…Only some scientists evaluate the effectiveness of the innovation activity of an enterprise. In particular, study [13] revealed a statistically significant positive relationship between enterprise investments in intellectual property and their results. In this case, one group of effectiveness indicators was based on the data on the income growth of enterprises.…”
Section: The Study Materials and Methodsmentioning
confidence: 89%
“…The devised integrated approach to assessing the indicators of innovativeness of the company's personnel differs from those discussed in this study [8][9][10][11][12][13][14][15][16] by the fact that:…”
Section: Discussion Of the Proposed Comprehensive Approach To The Assessment Of Indicators Of Innovativeness Of The Company's Personnelmentioning
confidence: 99%
See 1 more Smart Citation